Penerapan Prinsip-prinsip Feng Shui Aliran Bentuk Pada Desain Interior Rumah Tinggal di Surabaya Timur (Studi Kasus Rumah Tinggal Bapak Joyo) - Grace Mulyono, Erwin Pheter M. Sholahuddin (Intra, 2013)
Feng Shui and Interior Design are two arts which are closely related with residence. A house is a future saving that people might desire. There are many ways to make an ideal residential home, one of which is employing the principles of Feng Shui. A house that applies the principles of flow-forms Feng Shui on the interior is Mr. Joyos house located in a residential Regency 21, East Surabaya. This study aims to find out the principles of Feng Shui stream, implemented forms, and to determine the application of Feng Shui principles that shape the flow in Mr. Joyos residence in East Surabaya. This study uses qualitative deductive method. The study is began by collecting the data through interviews and observations, then looking for the principles of Feng Shui applied to the interior of the house and its application according to the literature analyzing the principles of flow-form Feng Shui on the interior of the house.